EFFECTS OF COCONUT WATER (COCOS NUCIFERA SP.) ADMINISTRATION AS PREVENTION OF UROLITHIASIS IN CALCIUM OXALATE INDUCED - WHITE RAT WISTAR STRAINS - Muhammad Reza Gautama; I Ketut Sudiana; Soetojo; Djojodimedjo, Tarmono (Indonesian Urological Association, 2021)
Objective: To analyze the effect of coconut water administration on the occurrence of urolithiasis in calcium oxalate-induced Wistar rats. Material & Methods: Laboratory experimental study with post-test only control group design, using experimental model of male Rattus norwegicus-Wistar strains. The treatment given is ad libitum administration coconut water to observe its effect on renal histopathological changes, microscopic analysis, and renal function markers. Urolithiasis induction uses exposure of 0.75% ethylene glycol (EG), and 2% Ammonium chloride (AC) in drinking water. Results: Descriptive analysis showed the tendency of decreasing in mean of renal function markers, and histopathological nephron damage in the treatment group versus control group: BUN (11.22 versus 14.29); Creatinine Serum (0.5308 versus 0.5714); degree of nephron damage (5.22 versus 10.36). In microscopic analysis, there were calcium deposits in the kidney tubules in the control group, which were not found in the treatment group. Based on the ANOVA test, obtained significant difference in BUN levels with p value=0.023 (p<0.05), and the degree of nephron damage between study groups with p value= 0.000 (p<0.05). There was no significant difference in serum creatinine with p value= 0.23 (p>0.05). Conclusion: Coconut water is potential modality in inhibiting the deposition of calcium oxalate crystals, and protecting from impaired kidney function against urolithiasis in animal-model of calcium oxalate-induced Wistar rats.